2023
DOI: 10.1002/smll.202301663
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of Protein Corona Formation around Nanoparticles: Old Puzzles and New Insights

Abstract: Although a wide variety of nanoparticles (NPs) have been engineered for use as disease markers or drug delivery agents, the number of nanomedicines in clinical use has hitherto remained small. A key obstacle in nanomedicine development is the lack of a deep mechanistic understanding of NP interactions in the bio‐environment. Here, the focus is on the biomolecular adsorption layer (protein corona), which quickly enshrouds a pristine NP exposed to a biofluid and modifies the way the NP interacts with the bio‐env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 236 publications
0
33
0
Order By: Relevance
“…This observation contrasts with part of the literature that observes multilayers on nanoparticles of similar sizes. , Lin et al, for example, observed effective thicknesses in excess of 13 nm for a similar system (gold nanorod in a protein mixture) and attributed this to the formation of multilayers . However, it is important to note that analysis techniques based on the measurement of size or mobility of NPs in solution (such as DLS) cannot distinguish between PC formation and particle clustering . RONAS is insensitive to aggregation and, therefore, accounts for PC formation exclusively.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…This observation contrasts with part of the literature that observes multilayers on nanoparticles of similar sizes. , Lin et al, for example, observed effective thicknesses in excess of 13 nm for a similar system (gold nanorod in a protein mixture) and attributed this to the formation of multilayers . However, it is important to note that analysis techniques based on the measurement of size or mobility of NPs in solution (such as DLS) cannot distinguish between PC formation and particle clustering . RONAS is insensitive to aggregation and, therefore, accounts for PC formation exclusively.…”
Section: Resultsmentioning
confidence: 72%
“…Indeed, it has been shown that proteins tend to rapidly form a weakly bound layer to the NPs, but as adsorption time increases, these weak interactions are progressively replaced by stronger (and eventually irreversible) interactions. , In addition, at low protein concentrations, the slow association rate enables the early adsorbed proteins to have more time to rearrange into a more stable configuration. These configurations, which may be structural relaxations, provide reduced space for subsequent proteins, resulting in a more compact PC structure . Taken together, these mechanisms explain the gradual plasmon shift for high dilution factors.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations